Secure Transmission and Intelligent Analysis of Demand-Side Data in Smart Grids: A 5G NB-IoT Framework - Shen, Yongpeng; He, Ting; Wang, Qian; Zhang, Junmin; Wang, Yanfeng (Frontiers in Energy Research, 2022)
In order to tap the advantages of Narrow Band-Internet of Things (NB-IoT) on the demand side of the smart grid, improve the security of information transmission and make use of demand-side data, we focus on the secure transmission, trusted services and intelligent analysis of “5G+Smart Grid”, and we construct a comprehensive solution consists of encrypted data terminals, management systems, and intelligent analysis methods. A 5G NB-IoT framework proposed in this paper can serve grid planning and demand response, it can further promote the deep integration of 5G and the smart grid. Therefore, this research will contribute to the implementation of a new generation of information technology on the smart grid, build a deep integration application scenario of the "5G+Smart Grid", improve the intelligence of the grids, and further promote the "dual carbon" goal of the power system.